Compradors as part of TCC: The case of Serbia - Antonić, Slobodan (Sociološki pregled, 2023)
In the first part of the article, the theoretical framework is given, and the economic and political reasons are presented as to why Serbia can be considered an “informal”, “structural” or “postmodern” colony. The standard method is explained of extracting surplus from the (semi)periphery countries of the world capitalist system and, in this respect, the example of Serbia is used to shows what one of the key comprador functions is. The second part of the article provides an overview of the viewpoints of social scientists in Serbia who applied the concept of the comprador bourgeoisie (or comprador elite) as part of the global class structure to contemporary Serbian society. Some conceptual dilemmas are also considered, as well as the possibility of further theoretical and empirical research of this issue in Serbian sociology.
Keywords: transnational capitalist class (TCC); neocolonialism; comprador elite; chained monopolism; world capitalist system